2015
DOI: 10.1016/j.schres.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Memories reactivated under ketamine are subsequently stronger: A potential pre-clinical behavioral model of psychosis

Abstract: Background Sub-anesthetic doses of the NMDA antagonist ketamine have been shown to model the formation and stability of delusion in human subjects. The later has been predicted to be due to aberrant prediction error resulting in enhanced destabilization of beliefs. To extend the scope of this model, we investigated the effect of administration of low dose systemic ketamine on memory in a rodent model of memory reconsolidation. Methods Systemic ketamine was administered either prior to or immediately followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 75 publications
0
19
1
Order By: Relevance
“…We thus chose a minimal dose of 10 mg/kg ( i.p. ) based on its ability to modulate conditioned fear in rats (Honsberger et al, 2015), and its antidepressant effects consistent throughout the literature (Carrier and Kabbaj, 2013; Li et al, 2010). Twenty-four hours later, the contextual fear memory was tested again in context A for 5 min.…”
Section: Methodsmentioning
confidence: 78%
“…We thus chose a minimal dose of 10 mg/kg ( i.p. ) based on its ability to modulate conditioned fear in rats (Honsberger et al, 2015), and its antidepressant effects consistent throughout the literature (Carrier and Kabbaj, 2013; Li et al, 2010). Twenty-four hours later, the contextual fear memory was tested again in context A for 5 min.…”
Section: Methodsmentioning
confidence: 78%
“…27 We have modeled this process in humans and rats with ketamine. 24 By creating new associations, reactivating them under ketamine, and then testing their strength, we observed that ketamine-reactivated associations were strengthened. 87 In humans, this effect correlated with ketamine-induced psychosis and PE brain signal.…”
Section: Delusion Persistencementioning
confidence: 90%
“…21 Ketamine, the N-methyl-D-aspartate (NMDA) glutamate receptor antagonist, transiently and reversibly engenders delusion-like ideas in healthy people 23 and other animals. 24 These delusions might be manifestations of aberrant PE, 8 the mismatch between our expectancy in a given situation and what we experience. 25 Derived from formal learning theory to explain mechanisms of animal conditioning, PE 25 is signaled by dopamine and glutamate activity in the brain.…”
Section: Drug Modelsmentioning
confidence: 99%
“…When subanesthetic ketamine is administered shortly before testing, contrasting anxiolytic (Engin et al, 2009; Zhang et al, 2015) and anxiogenic effects (da Silva et al, 2010; Silvestre et al, 1997) have been reported. In fear-conditioning studies, ketamine administered during fear memory reactivation has shown to both reduce (Duclot et al, 2016) and enhance conditioned fear (Honsberger et al, 2015). If we consider the magnitude of conditioned hyperarousal a reflection of an anxiogenic or fear state, our results suggest ketamine has no immediate effect on anxiety-like behavior, adding to the inconsistency within the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, our concerns about ketamine having sensory-motor effects on the eyeblink response precluded us from examining more immediate effects of ketamine (see Methods). Of importance is that others have reported effects of ketamine on anxiety-like or fear conditioned behaviors when tested a day after treatment (Babar et al, 2001; Honsberger et al, 2015), suggesting that any effects ketamine may have should last at least 24 hs. In addition, clinical reports of ketamine given to PTSD patients also mention effects lasting beyond one day (Feder et al, 2014).…”
Section: Discussionmentioning
confidence: 99%